Dorsal root ganglia volume is increased in patients with the Fabry-related GLA variant p.D313Y - Godel, Tim; Bäumer, Philipp; Kronlage, Moritz; Hayes, Jennifer; Heiland, Sabine; Bendszus, Martin (Journal of neurology, 2019)
Purpose: To examine dorsal root ganglia and proximal nerve segments in patients carrying the Fabry-related GLA-gene variant p.D313Y in comparison to patients with classical Fabry mutations and healthy controls by morphometric and functional magnetic resonance neurography. Methods: This prospective multicenter study examines the lumbosacral dorsal root ganglia and sciatic nerve in 11 female p.D313Y patients by a standardized magnetic resonance neurography protocol at 3 T. Volumes of dorsal root ganglia L3 to S2, permeability of dorsal root ganglia L5 and S1, and spinal nerve L5 as well as cross-sectional area of the sciatic nerve were assessed and compared to 10 females carrying a classical Fabry mutation and 16 healthy female controls. Results: Compared to healthy controls, dorsal root ganglia volumes of p.D313Y females were enlarged by 53% (L3), 48% (L4), 43% (L5), 57% (S1) (p < 0.001), and 55% (S2) (p < 0.05), but less pronounced compared to females carrying a classical Fabry mutation. Compared to healthy controls, p.D313Y patients showed no changes of dorsal root ganglia vascular permeability, while patients with a classical Fabry mutation showed a distinct decrease (p < 0.05). Sciatic nerve cross-sectional area was mildly increased by 6% in p.D313Y as well as in classical Fabry patients (p < 0.05). Conclusions: Patients carrying the GLA-gene variant p.D313Y show distinctly enlarged dorsal root ganglia, while vascular permeability remains within normal limits. Overall, these alterations partially share characteristics commonly seen in patients with a mutation causing classical FD. This suggests that p.D313Y causes a potentially treatable condition resembling an early stage of Fabry disease.